IMPLEMENTASI PROGRAM BEDAH POJOK BACA KELAS UNTUK MENINGKATKAN LITERASI SISWA DI SEKOLAH DASAR - Hijrawatil Aswat; Masri Masri; Nurmin Aminu; Fitriani B; Mitrakasih La Ode Onde; Eka Rosmitha Sari; Ahmadi Ashari (Universitas Muhammadiyah Luwuk, 2023)
The lack of availability of adequate classroom reading corners and attracting students' attention has an impact on students' reading interest. This activity aims to implement the Class Reading Corner Surgery Program as an effort to improve student literacy in elementary schools. The method used is a participatory approach through collaboration between the activity implementation team, teachers, and students. The first phase was conducted an initial survey to evaluate the existing condition of the reading corner and based on the survey results, the reading corner surgery program was designed by involving physical renovation, procurement of new books, and development of interesting activities to improve students' interest and reading skills. The results of this program show a positive impact on significantly improving student literacy in elementary schools. After going through the process of renovation and procurement of books, the reading corner in the classroom becomes more interesting and comfortable for students. This Class Reading Corner Surgery Program not only focuses on the physical aspect, but also pays attention to the development of students' reading interest and reading skills. With this program, it is expected that students' literacy in elementary schools can increase significantly, having a positive impact on their learning and development.